Fundamentals in Crafting Research and Community Service Articles - Sukmawati Hasan, Diana; S. Sangadji, Suwandi (PT. Sangadji Media Publishing, 2024)
The creation of research and community service articles is essential for advancing knowledge and societal development, serving as pillars in academia and community engagement. These articles go beyond mere documentation, incorporating methodological rigor, theoretical frameworks, and practical implications of research findings. Understanding the intricacies of crafting such articles reveals their role as instruments for fostering connections between academia and society. They contribute to the collective understanding of various phenomena and address societal issues, demanding intellectual honesty, transparency, and a pursuit of truth. Research articles illuminate theoretical landscapes, while community service articles bridge the gap between academia and everyday life, emphasizing practical applications. Crafting articles that seamlessly integrate both aspects requires a multidimensional approach, balancing theoretical depth with practical relevance. Research methodologies, ethical guidelines, and clear articulation of objectives form the bedrock of credible and impactful research articles. The symbiotic relationship between research and community service articles becomes apparent in their shared goal of societal betterment. Rigorous methodologies enhance credibility and study replicability, while theoretical frameworks provide conceptual underpinning. Effective crafting of community service articles involves communicating research outcomes and reflecting on implications for stakeholders. In the digital age, accessibility of information enables broader engagement through multimedia elements and interactive content. It is crucial to note the fundamental differences between research articles and community engagement articles, including concept, purpose, and content. Research articles highlight scientific findings, while community engagement articles focus on applying research to benefit society directly.